Measuring inner diameter of capillary tubes. Issue 1 (March 2021) - Fernandes, C; Almeida, A; Wolf, F G; Porath, M C
Abstract: The dimensional characterization of capillary tubes is a recurring issue in microfluidic applications, since they are often used to connect microfluidic devices to injection and monitoring systems. In this work three experimental methods were applied and discussed for measuring the inner diameter of thin tubes, allowing the comparison and determination of the most accurate procedure, taking into account the application and involved measurement uncertainty. The methods analysed are based on (i) sizing by stereo microscope software, (ii) image analysis (binarization) and (iii) internal fluid mass. The results show that the three methods applied can provide accurate values, but the best choice in terms of simplicity and efficiency is that one based on image analysis.